The Protective Regulatory Acts Applied to the Arms Industry and Its Consequences - Lamb, Gabriela Bratz (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2018)
The purpose of this paper is to identify the origins and consequences of Brazilian state regulatory acts for the acquisition of arms and related materials, focusing on those promoted by the Brazilian Army through a discretionary decision and by auxiliary security forces at the time of the bidding process. To do so, it will be necessary to demonstrate the legislative evolution that generated the current scenario of the arms trade in the country, and the conflicting administrative principles, especially those related to the bidding process, provided for in Law 8,666 of June 21, 1993. Through the economic analysis, therefore, the way and the ends intended by the legislation will be evidenced, evidencing if they are reached, and if beneficial.